PENGARUH KARAKTERISTIK PEKERJAAN, PENGEMBANGAN KARIR, DAN STRES KERJA TERHADAP KOMITMEN ORGANISASIONAL - Putri, Gitria Romadhona; Martono, S. (Management Analysis Journal, 2015)
The purpose of Â this research is to find out whether there is influence of the characteristics of employment, career development and work stress to organizational commitment. The population in this study were all employees PDAM Tirta Moedal Semarang is 531. The number of samples used in the study is 85 employees. The analysis model is multiple regression using programe SPSS 16.0. The result of this study showed that job characteristic has positive and significant effect to organizational commitment, career develepmont has positive and significant effect to organizational commitment, job stress has negative andÂ  significant effect to organizational commitment.